Análisis de la eficiencia y sus factores explicativos en el sector de consultoría y auditoría en Espa\~na - Justo de Jorge Moreno; Oscar Rojas Carrasco; Jorge Sánchez Henríquez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
– This work has been raised with the aim of analyzing the level of efficiency "benchmarking" and its explanatory factors of consulting audit firms in Spain. We have applied a semi-parametric model following the methodology of Simar and Wilson (2007). The main results show that five companies have been part of the definition of the frontier (best practice) Deloitte, PricewaterhouseCoopers, Ernest & Young, Audihispana Grant Thorton and Laplaza for the period 2006-2009. Market concentration, size, and specialization of the activities have proven to be factors explaining efficiency.
Keywords: C14; L84; 330; effciency; benchmarking; auditing and consulting firms; concentration; specialization